1996
DOI: 10.1002/(sici)1099-1085(199602)10:2<315::aid-hyp361>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic agents in freshwater resources

Abstract: Numerous pathogenic agents have been found in freshwaters used as sources for water supplies, recreational bathing and irrigation. These agents include bacterial pathogens, enteric viruses, several protozoans and parasitic worms more common to tropical waters. Although infected humans are a major source of pathogens, farm animals (cattle, sheep, pigs), animal pets (dogs, cats) and wildlife serve as significant reservoirs and should not be ignored. The range of infected individuals within a given warm-blooded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…In some studies a significant correlation has been found between the level of thermotolerant coliforms and the number of samples positive for certain pathogens (4,34). However, a poor correlation similar to that shown in the present study has also been demonstrated elsewhere (8, 14,26,43). The presence or absence of a correlation between fecal indicators and pathogens could reflect the occasional appearance of enteropathogens in surface waters and the different rates of survival and recovery of the pathogens compared with those of fecal indicators.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In some studies a significant correlation has been found between the level of thermotolerant coliforms and the number of samples positive for certain pathogens (4,34). However, a poor correlation similar to that shown in the present study has also been demonstrated elsewhere (8, 14,26,43). The presence or absence of a correlation between fecal indicators and pathogens could reflect the occasional appearance of enteropathogens in surface waters and the different rates of survival and recovery of the pathogens compared with those of fecal indicators.…”
Section: Discussionsupporting
confidence: 67%
“…The presence or absence of a correlation between fecal indicators and pathogens could reflect the occasional appearance of enteropathogens in surface waters and the different rates of survival and recovery of the pathogens compared with those of fecal indicators. One possible factor affecting the low correlation could also be different microbial densities in the original contamination sources, and therefore, the failure to detect pathogens was due to sampling volumes that were too small (14,17). For detection of Giardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these and other studies suggest that faecal indicators are potentially a useful warning of the potential presence of salmonellae in aquatic environments (Geldreich, 1996). However, relationships are not always found between faecal indicators and salmonellae in aquatic environments; an observation that may be related to various reasons such as different survival rates between salmonellae and faecal indicators, also the possibility that salmonellae being in a viable but nonculturable state.…”
Section: Aquatic Environmentsmentioning
confidence: 69%
“…Faecal pollution in rivers has been reported in Malaysia (Law 1980;Kenzaka et al 2001). The main sources of faecal contamination are poultry manure, agricultural runoff, industrial waste, poorly treated or untreated sewage from urban areas and other anthropogenic input (Geldreich 1996;Ferguson et al 2003;Wilkinson et al 2006). As shown by the correlation coefficient, salinity explicated about 22 % of change in coliform counts, therefore, other factors, e.g.…”
Section: Distribution Of Coliform and E Colimentioning
confidence: 99%
“…Faecal pollution can be introduced from multiple sources, e.g. agricultural runoff, industrial waste, inadequately treated sewage from urban areas and other anthropogenic input (Geldreich 1996;Ferguson et al 2003).…”
Section: Introductionmentioning
confidence: 99%